Tytulatura rodu von Promnitz z linii żarskiej w XVI-XVIII wieku w świetle rękopisów i starodruków = The titulature of the von Promnitz family of the Żary lineage in 16-18th centuries in a light of the old prints and manuscripts - Maciejewski, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the evolution of titulature of the von Promnitz family of the Żary (Sorau) lineage. Its development was similar to the majority of noble clans in Silesia. Members of the von Promnitz ancestry within 16-18th centuries gained ever higher aristocratic titles. Starting from the Baron, then Count, and ending with the Duke - unfortunately the latter title could only be used by two representatives of the ancestry (on an ad personam rule). The source material was based on the manuscripts found in the resources of the State Archives in Zielona Gora and old prints of digital libraries in Poland and Germany.
Keywords: szlachta; tytuły; Żary; Promnitz, von; Nobility; titles